Positive Effects of Nature on Cognitive Performance Across Multiple Experiments: Test Order but Not Affect Modulates the Cognitive Effects - Stenfors, Cecilia U. D.; Van Hedger, Stephen C.; Schertz, Kathryn E.; Meyer, Francisco A. C.; Smith, Karen E. L.; Norman, Greg J.; Bourrier, Stefan C.; Enns, James T.; Kardan, Omid; Jonides, John; Berman, Marc G. (Frontiers in Psychology, 2019)
Interactions with natural environments and nature-related stimuli have been found to be beneficial to cognitive performance, in particular on executive cognitive tasks with high demands on directed attention processes. However, results vary across different studies. The aim of the present paper was to evaluate the effects of nature versus urban environments on cognitive performance across all of our published and new/unpublished studies testing the effects of different interactions with nature versus urban/built control environments, on an executive-functioning test with high demands on directed attention – the backwards digit span (BDS) task. Specific aims in this study were to: 1) evaluate the effect of nature versus urban environment interactions on BDS across different exposure types (e.g. real-world vs. artificial environments/stimuli); 2) disentangle the effects of testing order (i.e. effects caused by the order in which experimental conditions are administered) from the effects of the environment interactions, and 3) test the (mediating) role of affective changes on BDS performance. To this end, data from 13 experiments are presented, and pooled data-analyses are performed. Results from the pooled data-analyses (N=528 participants) showed significant time-by-environment interactions with beneficial effects of nature compared to urban environments on BDS performance. There were also clear interactions with the order in which environment conditions were tested. Specifically, there were practice effects across environment conditions in first sessions. Importantly, after parceling out initial practice effects, the positive effects of nature compared to urban interactions on BDS performance were magnified. Changes in positive or negative affect did not mediate the beneficial effects of nature on BDS performance. These results are discussed in relation to the findings of other studies identified in the literature. Uncontrolled and confounding order effects (i.e., effects due to the order of experimental conditions, rather than the treatment conditions) may explain some of the inconsistent findings across studies in the literature on nature effects on cognitive performance. In all, these results highlight the robustness of the effects of natural environments on cognition, particularly when confounding order effects have been considered, and provide a more nuanced account of when a nature intervention will be most effective.